Strategy For Strengthening Business Incubators As Establishment Of Entrepreneurship Using The Anp Model In Private Higher Education In North Sumatera - Nawir Yuslem; Zuhrinal M Nawawi; Siregar Dahrul (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The high level of educated unemployment is the responsibility of Universities to have a sustainable business by implementing mentoring and strengthening new entrepreneurial institutions, namely through the Business Incubator. The problems found in this research internally come from regulations, lecturers, digitization and infrastructure, while external problems come from problems with the partner network, environment and funding. Based on the results of the research that has been done, regulatory issues are a top priority in the strategy for strengthening entrepreneurship as a form of business incubator for private tertiary institutions in North Sumatra with a score of 0.298. Furthermore, the second priority problem is the problem of facilities and infrastructure with a value of 0.1197. Furthermore, the third priority problem is facilities and infrastructure with a value of 0.1196. In determining the order of priority, respondents have an agreement (W) of 0.024.